A corded-mixed bell beaker vase at the monumental enclosure of Forca, Maia, North of Portugal - Bettencourt, Ana M. S. (2011)
The aim of this work is to present a fragment of a corded bell beaker vase (CZ/M) identified at the archaeological site of Forca/Lavra, in North-west of Portugal. Forca is a place that contains monumental structures, similar to other enclosures of the Iberian Peninsula. In Forca, ditches and palisades were built, containing internal fences, pits structures and fireplaces in use, at least, between the Chalcolithic and Bronze Ages. The fragment of the bell beaker vessel appeared inside a ditch, in a Chalcolithic context associated with a radiocarbon date from 2.625 to 2.337 BC. Corded bell beaker vases are rare in the Iberian Peninsula and known only in three other Portuguese prehistoric sites: the enclosure of Porto Torrão, Ferreira do Alentejo, in the Southwest, and the walled enclosures of Castelo Velho de Freixo de Numão and Castanheiro do Vento, both places are located in Vila Nova de Foz Côa, in the Northwest. The first one appeared inside a Chalcolithic level, the second one was in from the beginning of the third quarter of the third millennia BC, and the third one, still unpublished, is also surely of the third millennium BC. Based on its rarity and on these contexts of findings the authors consider the hypothesis that this kind of bell beaker may have been used in a very special way of action and have circulated mainly in places of great importance, collectively serving a significant population group.